Producing and consuming urban planning exhibition halls in contemporary China. (November 2015) - Fan, Peilei
As if trying to seek order among the chaos, urban planning exhibition halls, a unique creation of China's planning manifesto during the market reform period, have started to appear on the horizon in many cities since the 2000s. This paper examines the production of planning exhibition halls and evaluates their use. It analyses how local governments have used urban planning exhibition halls to perform a set of functions: to prepare the mass audience for its grand future vision, to legitimate government plans for (re)development, to present the edited local history, to promote/glorify the mega events/projects, to spread particular propaganda and to manipulate citizen participation. Further, it finds that while most visitors are satisfied with the information dissemination function, they are disappointed at limited public participation opportunities, poorly presented cultural heritage and inadequately preserved city memory regarding its past plans.